2009
DOI: 10.1210/en.2009-0434
|View full text |Cite
|
Sign up to set email alerts
|

T Helper Type 17 Immune Response Plays an Indispensable Role for Development of Iodine-Induced Autoimmune Thyroiditis in Nonobese Diabetic-H2h4 Mice

Abstract: T helper type 1(Th1)/Th2 paradigm has been expanded by discovery of a novel effector T cell (T(eff)) subset, Th17 cells, which produce a proinflammatory cytokine IL-17. Th17 cells have recently been shown to play a major role in numerous autoimmune diseases that had previously been thought to be Th1-dominant diseases. We here studied the significance of Th17 cells in iodine-induced autoimmune thyroiditis in nonobese diabetic-H2(h4) mice, a mouse model of Hashimoto's thyroiditis in humans, which spontaneously d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(37 citation statements)
references
References 41 publications
4
32
0
1
Order By: Relevance
“…reported in their study on 13 HT patients, reachs statistical relevance in our study, due to the high number of subjects studied. These data suggest that IL-23 is involved in the development of HT and further support the role of Th17 cells in AITD, in line with the data from the literature [7][8][9]21]. An enhanced production of IL-23 by APCs may drive the immune response towards a Th17 phenotype and contribute to promote the autoimmune inflammation of the gland.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…reported in their study on 13 HT patients, reachs statistical relevance in our study, due to the high number of subjects studied. These data suggest that IL-23 is involved in the development of HT and further support the role of Th17 cells in AITD, in line with the data from the literature [7][8][9]21]. An enhanced production of IL-23 by APCs may drive the immune response towards a Th17 phenotype and contribute to promote the autoimmune inflammation of the gland.…”
Section: Resultssupporting
confidence: 88%
“…A real-time 2D apparatus (General Electric IL-17, IL-21 and IL-22, is involved in numerous autoimmune diseases (AID) commonly thought to be Th1 diseases, including HT [6][7][8][9]. Moreover, the proportion of peripheral Th17 cells has been found to be higher in patients affected by severe GD than in GD patients in remission [9].…”
Section: Methodsmentioning
confidence: 99%
“…Wang et al found direct injection of TNF-α into the thyroids of mTg-primed mice can induce thyrocyte apoptosis, indicating that pro-inflammatory TNF-α may play a critical role in thyroid destruction [14]. Horie I et al disclosed Th17 cells are critical for the pathogenesis of spontaneous autoimmune thyroiditis while Th17 cells were also shown to induce GD in NOD-H2(h4), but not in BALB/c mice, thus showing that the effect of IL-17 may also differ with the genetic background [15,16].…”
Section: Thyroid Function Test and Antithyroid Antibodiesmentioning
confidence: 99%
“…Previous studies have shown that Th17 cells have a key, independent role in thyroiditis in NOD.H-2 h4 mice [14]. To the best of our knowledge, this is the first report of Th22 cells in NOD.H-2 h4 mice.…”
Section: Disclosurementioning
confidence: 50%